Pengaruh Kegiatan Promosi Terhadap Keputusan Pembelian Konsumen Pada Produk Hana Collection - Audina Rizka Zahra; Zuhrinal M. Nawawi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study focuses on how the influence of promotional activities on consumer purchasing decisions on Hana Collection products. The purpose of this study is to determine how much influence promotional activities have on consumer purchasing decisions on Hana Collection products. The method used in this research is to use a qualitative method, namely by understanding the phenomenon of what is experienced by the research subjects as a whole by way of description. The results of the research achieved are that Hana Collection is more dominant in carrying out promotional techniques through social media, because nowadays it is more advanced and the era of gadgets. Various promotional techniques on social media are carried out by Hana Collection, namely by doing giveaways, giving discounts (discounts) and also giving cashback to consumers. Keywords: Promotion, Purchase decision, Consumer